The Bible in Buffalo Country Oenpelli Mission 1925-1931 - May, Sally K. (Aboriginal History Monographs, 2020)
Arriving in the remote Arnhem Land Aboriginal settlement of Oenpelli (Gunbalanya) in 1925, Alf and Mary Dyer aimed to bring Christ to a former buffalo shooting camp and an Aboriginal population many whites considered difficult to control. The Bible in Buffalo Country: Oenpelli Mission 1925-1931 represents a snapshot of the tumultuous first six years of the Church Missionary Society's mission at Oenpelli and the superintendency of Alfred Dyer between 1925 and 1931. Drawing together documentary and photographic sources with local community memory, a story emerges of miscommunication, sickness, constant logistical issues, and an Aboriginal community choosing when and how to engage with the newcomers to their land. This book provides a fascinating and detailed record of the primary sources of the mission, placed alongside the interpretation and insight of local Traditional Owners. Its contents include the historical and archaeological context of the primary source material, the vivid mission reports and correspondence, along with stunning photographs of the mission and relevant maps, and finally the oral history of Esther Manakgu, presenting Aboriginal memory of this complex era. The Bible in Buffalo Country emerged from community desire for access to the source documents of their own history and for their story to be known by the broader Australian public. It is intended for the benefit of communities in western Arnhem Land and is also a rich resource for historians of Aboriginal history (and other scholars in relevant disciplines).